Comparison Of Consumer Preferences And Satisfaction Factors In Offline And Online Shopping At Missyshop Official - Hery Maulana Arif; Deddy Ibrahim Rauf (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
This research aims to identify comparisons of consumer preferences between offline and online shopping at Missyshop Official and the factors that influence consumer satisfaction in both methods. Data collection was done through a questionnaire survey distributed to 90 Missyshop Official consumers in Makassar, Indonesia. The data obtained was analyzed using qualitative analysis. The research results show that consumer preference for offline shopping (69%) is higher than online shopping (31%). The factors that influence consumer satisfaction in offline and online shopping are product, price, and service. The level of consumer satisfaction when shopping offline (average score 3.40) and online (average score 3.08) is equally high. The most important factor in consumer satisfaction when shopping offline is service, followed by product, and then price. Meanwhile, when shopping online, product dimensions are the most important factor, followed by price and service.